A silver-doped hard carbon composite material, and its preparation method and application

By pretreating hard carbon materials and reacting silver mirrors, combined with lithium salt prelithiation treatment, the problem of low specific capacity and first-time efficiency of hard carbon materials in lithium-ion batteries is solved, and the electronic conductivity and magnification performance is improved, which significantly increases the performance of electronics. Improved overall performance of the material.

CN115513453BActive Publication Date: 2025-01-03SHENZHEN GOLD MEDAL NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211215799.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-30
Publication Date
2025-01-03
Estimated Expiration
2042-09-30

AI Technical Summary

Technical Problem

Hard carbon materials have problems such as low specific capacity, low first-time efficiency and low electronic conductivity in lithium-ion battery applications, and the nano-silver loading effect is poor, which affects the material's cycling performance and rate discharge performance.

Method used

By pretreating the hard carbon material to form carboxylated hard carbon, nanosilver doping is performed using silver mirror reaction, and prelithiation is carried out with lithium salt, so as to improve the load uniformity and bonding of nanosilver and improve the electronics of the material Conductivity and first-time efficiency.

Benefits of technology

The specific capacity is increased to ≥450mAh/g, the first efficiency is increased to ≥85%, and the rate performance and cyclic performance of the material are significantly improved, the probability of side reactions is reduced, and the overall performance of the electrode material is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115513453B_ABST
    Figure CN115513453B_ABST
Patent Text Reader

Abstract

The embodiment of the present invention discloses a silver-doped hard carbon composite material, which is obtained by carboxylating hard carbon, mixing it with a silver ammonia solution and a formaldehyde solution to load silver, and then mixing it with an organic solution of a lithium salt for pre-lithiation, and then carbonizing it. The present invention uses a silver mirror reaction to load nanosilver on the hard carbon material. During the silver mirror reaction, silver ions will gradually deposit on the hard carbon material to form a large number of nanosilver particles, making the silver distribution more uniform and the binding of nanosilver to the hard carbon material stronger. The hard carbon precursor is carboxylated, and the acidic groups on the surface of the carboxylated hard carbon will destroy the conversion balance of the silver ammonia complex ions in the alkaline silver ammonia solution, making it easier for nanosilver to deposit and grow on the surface of the carboxylated hard carbon grafted with acidic groups, and finally forming nanosilver particles with higher binding strength to the surface of the carboxylated hard carbon. The present invention improves the electronic conductivity of the material, improves the rate performance and increases its first efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium ion battery materials, and specifically relates to a silver-doped hard carbon composite material and a preparation method and application thereof. Background Art

[0002] Hard carbon is an amorphous carbon material that is difficult to graphitize. It has become the preferred material in HEV, 48V and other fields due to its advantages such as good fast charging performance, excellent low-temperature performance and zero expansion. However, hard carbon has problems such as low specific capacity (300mAh / g) and low first efficiency (80%), which has limited its promotion and application in EV and other fields. Hard carbon materials have a porous structure. On the one hand, they store lithium ions to reduce the specific capacity and produce side reactions to reduce the first efficiency of the material. On the other hand, the porous structure causes poor contact between materials, resulting in low electronic conductivity. Although there are methods on the market to increase the specific capacity of material processing by doping with phosphorus and boron, the impedance of the material is too large and the voltage platform is too high, which affects the energy density of the whole battery. One of the measures to improve the electronic conductivity of the porous material structure is to fill the pores of the hard carbon material with highly conductive nanometal materials to reduce impedance and improve first efficiency.

[0003] For example, the patent document with patent application number CN201710210540.6 discloses a method for preparing a double-coated lithium-ion battery negative electrode material, which includes the following steps: preparing a silver-ammonia solution; dispersing a carbon-based material into the silver-ammonia solution, adding a reducing agent thereto to react with silver and ammonia, and depositing silver nanoparticles on the surface of the carbon-based material; drying the reacted silver-ammonia solution to obtain a precursor; treating the precursor at 250 to 550°C for 3 to 8 hours to obtain a double-coated lithium-ion battery negative electrode material. This patent doped nanosilver into the carbon-based material to reduce the interfacial potential energy of the composite material system, so that the negative electrode material has excellent cycle performance and rate discharge performance, and its low-temperature performance is significantly improved, but the loading rate of nanosilver on the carbon-based material in this solution is not good, and the first efficiency needs to be improved. Summary of the invention

[0004] In order to address the deficiencies in the prior art, the present invention provides a silver-doped hard carbon composite material. The hard carbon material is first pretreated and then loaded with silver by a silver mirror reaction, so that the silver doping is more uniform, the loading amount is larger, the bonding is better, the electronic conductivity of the material is increased, and the rate performance is improved; the hard carbon material is then pre-lithiated to improve its initial efficiency.

[0005] In order to achieve the above technical objectives, the technical solution adopted by the present invention is as follows:

[0006] The technical purpose of the first aspect of the present invention is to provide a method for preparing a silver-doped hard carbon composite material, comprising the following steps:

[0007] Pretreatment of hard carbon materials: soaking the hard carbon precursor in an acid solution to obtain carboxylated hard carbon;

[0008] Preparation of silver ammonia solution: mixing silver nitrate solution and ammonia solution to obtain silver ammonia solution;

[0009] Silver doping reaction: mixing the pretreated hard carbon material and the silver ammonia solution, adjusting the pH value to 9-10, adding formaldehyde solution, reacting at a temperature of 50-100° C., filtering and drying to obtain a silver-doped hard carbon precursor;

[0010] Pre-lithiation of hard carbon: mixing a silver-doped hard carbon precursor with an organic solution of a lithium salt, spray drying, and carbonizing under an inert atmosphere to obtain the silver-doped hard carbon composite material.

[0011] In the above preparation method, the acid solution is selected from at least one of sulfuric acid, hydrochloric acid, nitric acid and phosphoric acid, and the mass concentration of the acid solution is 5-20%.

[0012] In the above preparation method, the hard carbon precursor and the acid solution are mixed and treated at 50-100° C. for 24-72 hours. More preferably, the above treatment process is supplemented with ultrasonic stirring to make the two react more fully.

[0013] In the above preparation method, when preparing the silver ammonia solution, the mass concentration of the silver nitrate solution is 1-5%, the mass concentration of the ammonia solution is 5-20%, and the mass concentration of the formed silver ammonia solution is 3-15%.

[0014] In the above preparation method, the volume ratio of the silver nitrate solution to the ammonia solution is 1:(1-2).

[0015] In the above preparation method, the mass concentration of the formaldehyde solution is 1-5%.

[0016] In the above preparation method, in the silver doping reaction, the mixing ratio of the carboxylated hard carbon, silver ammonia solution and formaldehyde is 10-50g:100mL:10-50mL.

[0017] In the above preparation method, after the silver doping reaction is completed, the drying is vacuum drying.

[0018] In the above preparation method, the lithium salt is selected from one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate and lithium difluorophosphate.

[0019] In the above preparation method, the organic solution is selected from one or more of esters, ethers, alcohols and nitriles, and more specifically, is selected from at least one of ethanol, butanediol, ethylene glycol, acetonitrile, dimethyl carbonate and diethyl ether.

[0020] In the above preparation method, the mass concentration of lithium salt in the organic solution of lithium salt is 1-10%.

[0021] In the above preparation method, the mass ratio of the silver-doped hard carbon precursor to the lithium salt is 100:(1-5).

[0022] In the above preparation method, the carbonization temperature is 800-1000°C.

[0023] The technical purpose of the second aspect of the present invention is to provide a silver-doped hard carbon composite material prepared by the above method.

[0024] The present invention uses a silver mirror reaction to load nanosilver on hard carbon materials. During the silver mirror reaction, silver ions will gradually deposit on the hard carbon materials to form a large number of nanosilver particles. Compared with the traditional solid-phase doping method, the distribution of nanosilver on hard carbon can be more uniform, and the binding of nanosilver to hard carbon materials is stronger. In the technical scheme of the present invention, before nanosilver loading, the hard carbon precursor is pretreated with dilute acid to graft acidic groups such as carboxyl groups on the surface of the hard carbon precursor to obtain carboxylated hard carbon. When the carboxylated hard carbon is added to the silver ammonia solution, the acidic groups on the surface of the carboxylated hard carbon will destroy the silver ammonia complex ion conversion balance in the alkaline silver ammonia solution, making it easier for nanosilver to deposit and grow on the surface of the carboxylated hard carbon grafted with acidic groups, and finally forming nanosilver particles with higher binding strength to the surface of the carboxylated hard carbon.

[0025] After silver doping is performed on carboxylated hard carbon, the present invention also uses lithium salt to perform pre-lithiation treatment on it, in order to improve the first efficiency of the electrode material. In the preparation method of the present invention, based on the pre-processing, lithium and silver are easily combined to form silver-lithium alloy, thereby improving the binding stability of lithium on the hard carbon material. It should be noted that the order between the steps of silver doping reaction and hard carbon pre-lithiation of the present invention cannot be changed. If pre-lithiation treatment is performed first and then silver doping is performed, on the one hand, due to the lack of the binding effect of nanosilver in the pre-lithiation process, it is difficult for hard carbon and lithium to interact to form a lithium alloy, resulting in a greatly reduced pre-lithiation effect. Therefore, the purpose of the silver doping reaction is not only to dope nanosilver into the hard carbon material, but also to improve the subsequent pre-lithiation effect; on the other hand, the pre-lithiation treatment will also affect the subsequent silver loading to a certain extent. Through the pre-lithiation process of the present invention, a stable structure is formed between lithium ions and the electrode material. On the one hand, the filling of nanosilver avoids the loss of lithium ions caused by a large number of pores in the hard carbon during the electrode reaction, and on the other hand, it also avoids the loss caused by the combination of nanosilver and lithium ions, thereby improving the first efficiency.

[0026] The technical purpose of the third aspect of the present invention is to provide the application of the silver-doped hard carbon composite material as a negative electrode material for a battery.

[0027] The silver-doped hard carbon composite material prepared by the method of the present invention has a specific capacity of ≥450 mAh / g, a first efficiency of ≥85%, a tap density of ≥0.9 g / cm3, and a powder OI value of ≤3 as a negative electrode material.

[0028] Implementing the embodiments of the present invention will have the following beneficial effects:

[0029] (1) The present invention fills nanosilver material in hard carbon, which, on the one hand, solves the problem of low electronic conductivity of hard carbon material caused by the presence of pores, and on the other hand, reduces the contact area between the pores and the electrolyte, thereby reducing the probability of side reactions.

[0030] (2) The present invention first performs a carboxylic acid modification treatment on the hard carbon material to graft carboxyl groups on its surface. The acidic carboxyl groups promote the occurrence of silver-ammonia reaction, allowing nanosilver to grow and deposit on the hard carbon material, thereby improving the uniformity and density of doping. Compared with the prior art, it has the characteristics of good uniformity and high contact between silver and carbon, thereby improving the electronic conductivity of the material and the rate performance of the material.

[0031] (3) After the nano-silver doping, the present invention performs a pre-lithiation treatment on the hard carbon material to improve the initial efficiency. At the same time, silver and lithium are combined to easily form a silver-lithium oxide alloy, thereby improving the bonding stability of lithium on the hard carbon material. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0033] in:

[0034] Figure 1 This is the SEM image of the silver-doped hard carbon composite material prepared in Example 1. DETAILED DESCRIPTION

[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] In Examples 1-3, silver-doped hard carbon composite materials were prepared:

[0037] The hard carbon precursor used in the following examples was prepared by the following method:

[0038] Weigh 30 g of phenolic resin and stir to dissolve it in 60 mL of anhydrous ethanol, filter out impurities, and then vacuum dry it at 80°C for 24 h. Carbonize it at 1200°C for 3 h at a heating rate of 5°C / min under an argon atmosphere, ball mill it, and use a 600-mesh sieve to obtain a hard carbon precursor.

[0039] Example 1

[0040] S1, pretreatment of hard carbon material: 100 g of hard carbon precursor was immersed in 1000 mL of a 10% dilute nitric acid solution, ultrasonically stirred at 80°C for 24 h, immersed for 48 h, and then washed with deionized water to obtain carboxylated hard carbon;

[0041] S2, preparing a silver ammonia solution: dropping 100 mL of a 3% silver nitrate solution into 150 mL of a 15% ammonia solution to form a 9% silver ammonia solution;

[0042] S3, silver doping reaction: take 100 mL of the silver ammonia solution prepared in S2, add 30 g of the carboxylated hard carbon prepared in S1 and 30 mL of a formaldehyde solution with a mass concentration of 3%, adjust the pH value to 9 and perform magnetic stirring, make the silver ammonia solution react at 80°C, then filter, and vacuum dry the solid at 80°C for 24 hours to obtain a silver-doped hard carbon precursor;

[0043] S4, pre-lithiation of hard carbon: 100 g of the silver-doped hard carbon precursor prepared in S3 was transferred to 60 mL of an ethanol organic solution containing 5 wt% lithium difluorooxalatoborate, followed by spray drying. The solid was then transferred to a tubular furnace and heated to 900 °C for carbonization for 3 h under an inert atmosphere to obtain a silver-doped hard carbon composite material.

[0044] Example 2

[0045] S1, preparing a silver ammonia solution: dropping 100 mL of a 1% silver nitrate solution into 100 mL of a 5% ammonia solution to form a 3% silver ammonia solution;

[0046] S2, pretreatment of hard carbon material: 100 g of hard carbon precursor was immersed in 1000 mL of a dilute nitric acid solution with a mass concentration of 20%, ultrasonically stirred for 24 h and immersed for 48 h at a temperature of 50 ° C, and then washed with deionized water to obtain carboxylated hard carbon;

[0047] S3, silver doping reaction: take 100 mL of the silver ammonia solution prepared in S1, add 10 g of the carboxylated hard carbon prepared in S2 and 10 mL of a 3% formaldehyde solution, adjust the pH value to 9 and perform magnetic stirring, allow the silver ammonia solution to undergo a silver ammonia reaction at 50°C, then filter, and vacuum dry the solid at 80°C for 24 hours to obtain a silver-doped hard carbon precursor;

[0048] S4, pre-lithiation of hard carbon: 100 g of the silver-doped hard carbon precursor prepared in S3 was transferred to 500 mL of an acetonitrile organic solution containing 1 wt% of lithium difluorooxalatoborate, and then spray-dried. The solid was then transferred to a tubular furnace and heated to 800°C under an inert atmosphere for carbonization for 6 h to obtain a silver-doped hard carbon composite material.

[0049] Example 3

[0050] S1, preparing a silver ammonia solution: dropping 100 mL of a 5% silver nitrate solution into 200 mL of a 20% ammonia solution to form a 15% silver ammonia solution;

[0051] S2, pretreatment of hard carbon material: 100 g of hard carbon precursor was immersed in 1000 mL of a 5% dilute nitric acid solution, ultrasonically stirred for 24 h and immersed for 72 h at a temperature of 100 °C, and then washed with deionized water to obtain carboxylated hard carbon;

[0052] S3, silver doping reaction: take 100 mL of the silver ammonia solution prepared in S1, add 50 g of the carboxylated hard carbon prepared in S2 and 50 mL of a 2% formaldehyde solution, adjust the pH value to 10 and perform magnetic stirring, make the silver ammonia solution react with silver at 100°C, then filter, and vacuum dry the solid at 80°C for 24 hours to obtain a silver-doped hard carbon precursor;

[0053] S4, pre-lithiation of hard carbon: 100 g of the silver-doped hard carbon precursor prepared in S3 was transferred to 500 mL of an organic solution of dimethyl carbonate (DMC) containing 1 wt% of lithium difluorooxalatoborate, followed by spray drying. The solid was then transferred to a tubular furnace and heated to 1000°C under an argon inert atmosphere for carbonization for 1 h to obtain a silver-doped hard carbon composite material.

[0054] Comparative Example 1

[0055] 100 g of the hard carbon material in Example 1 and 5 g of nano silver powder were mixed evenly by a ball mill, and then the mixed powder was added to 500 mL of an ethanol organic solution containing 10% lithium difluorooxalate borate, spray dried, and then the dried solid was transferred to a tubular furnace, heated to 1000°C in an argon inert atmosphere and carbonized for 1 hour to obtain a silver-doped hard carbon composite material.

[0056] Comparative Example 2

[0057] Except for not performing the hard carbon material pretreatment process of S2, other operation processes are the same as Example 1 to obtain a silver-doped hard carbon composite material.

[0058] Comparative Example 3

[0059] S1, pretreatment of hard carbon material: 100 g of hard carbon precursor was immersed in 1000 mL of a 10% dilute nitric acid solution, ultrasonically stirred at 80°C for 24 h, immersed for 48 h, and then washed with deionized water to obtain carboxylated hard carbon;

[0060] S2, pre-lithiation of hard carbon: 100 g of the carboxylated hard carbon prepared in S1 was transferred into 60 mL of an ethanol organic solution containing 5 wt% lithium difluorooxalatoborate, and then spray-dried to obtain a pre-lithiation hard carbon precursor;

[0061] S3, preparing a silver ammonia solution: dropping 100 mL of a 3% silver nitrate solution into 150 mL of a 15% ammonia solution to form a 9% silver ammonia solution;

[0062] S4, silver doping reaction: take 100mL of the silver ammonia solution prepared in S3, add 30g of the pre-lithiated hard carbon precursor prepared in S2 thereto, adjust the pH value to 9 and perform magnetic stirring, so that the silver ammonia solution undergoes silver ammonia reaction at 80°C, then filter, vacuum dry the solid at 80°C for 24h, transfer the solid to a tubular furnace, raise the temperature to 900°C under an inert atmosphere and carbonize for 3h to obtain a silver-doped hard carbon composite material.

[0063] Performance tests of the materials prepared in the above examples and comparative examples:

[0064] (1) SEM test

[0065] The silver-doped hard carbon composite material prepared in Example 1 was subjected to SEM testing, and the test results are as follows: Figure 1 shown.

[0066] Depend on Figure 1 It can be seen that the composite material prepared in Example 1 presents a spherical structure with uniform size distribution and a particle size ranging from 5 to 15 μm.

[0067] (2) Physical and chemical properties and button battery testing

[0068] The composite materials prepared in Examples 1-3 and Comparative Examples 1-3 were tested for particle size, tap density, specific surface area, interlayer spacing, silver trace element content, powder resistivity, and powder OI value. The test was conducted according to the method of national standard GBT-24533-2019 "Graphite Anode Materials for Lithium Ion Batteries". The test results are shown in Table 1.

[0069] Table 1

[0070]

[0071] The composite materials in Examples 1-3 and Comparative Examples 1-3 were used as negative electrode materials for lithium-ion batteries and assembled into button batteries. The specific preparation method of the negative electrode material was as follows: adding a binder, a conductive agent and a solvent to the composite material, stirring and slurrying, coating on a copper foil, drying and rolling. The binder used was LA132 binder, the conductive agent was SP, and the solvent was double distilled water. According to the composite material: SP: LA132: double distilled water = 90g: 3g: 7g: 220mL, a negative electrode sheet was prepared; a metal lithium sheet was used as a counter electrode; the electrolyte was LiPF 6 / EC+DEC, LiPF in electrolyte 6 The electrolyte is a mixture of EC and DEC with a volume ratio of 1:1 as the solvent, and the electrolyte concentration is 1.3 mol / L; the diaphragm is a polyethylene PE film. The button cell is assembled in an argon-filled glove box. The electrochemical performance is carried out on a Wuhan Blue Electric CT2001A battery tester, with a charge and discharge voltage range of 0.00V to 2.0V and a charge and discharge rate of 0.1C. The first discharge capacity and first efficiency of the button cell are tested, and the rate performance (2C, 0.1C) and cycle performance (0.2C / 0.2C, 200 times) are tested at the same time. The test results are shown in Table 2.

[0072] Table 2

[0073]

[0074] It can be seen from Table 1 and Table 2 that the material prepared in the embodiment of the present invention has high specific capacity and first efficiency. The reason is that filling silver in the hard carbon material improves the electronic conductivity, and improves the rate and cycle performance; at the same time, the silver material has the characteristic of high tap density, which improves the tap density of the material, and silver has a catalytic effect. During the carbonization process of the material, a hard carbon material with a high interlayer spacing can be generated, and the rate performance is improved; and the material is pre-lithiumed with lithium difluorooxalatoborate to improve the first efficiency of the material.

[0075] (3) Soft pack battery test:

[0076] The composite materials in Examples 1-3 and Comparative Examples 1-3 were mixed and coated to prepare negative electrode sheets. 1 / 3Co 1 / 3 Mn 1 / 3 O 2 ) as the positive electrode, LiPF 6 (solvent is EC+DEC, volume ratio is 1:1, electrolyte concentration is 1.3 mol / L) as electrolyte, Celgard2400 membrane as separator, and a 2Ah soft-pack battery is prepared.

[0077] The rate performance of the soft pack battery was tested with a charge and discharge voltage range of 2.8 to 4.2 V, a temperature of 25 ± 3.0 °C, and charging at 1.0 C, 3.0 C, 5.0 C, 10.0 C, and 20. C, and discharging at 1.0 C. The results are shown in Table 3.

[0078] Table 3

[0079]

[0080]

[0081] It can be seen from Table 3 that the rate charging performance of the soft-pack batteries prepared with the materials of Examples 1-3 is significantly better than that of Comparative Examples 1-3, that is, the charging time is shorter. The reason for this is that the migration of lithium ions is required during the battery charging process, and the hard carbon of the negative electrode material in the embodiment is doped with silver with high electronic conductivity to reduce impedance. At the same time, lithium difluorooxalatoborate is pre-lithiated on the hard carbon material to increase the number of lithium ions during the charging and discharging process, thereby improving the rate performance and reducing the temperature rise.

[0082] (4) Cyclic performance test:

[0083] The cycle performance test conditions are: charge and discharge current 3C / 3C, voltage range 2.5-4.2V, cycle number 500 times. The test results are shown in Table 4.

[0084] (5) High temperature storage test: 55°C, 30 days, test its full charge capacity recovery. The test results are shown in Table 4.

[0085] Table 4

[0086]

[0087] As can be seen from Table 4, the cycle performance of the lithium-ion battery prepared using the composite material obtained in Examples 1-3 is significantly better than that of the comparative example in all stages. The reason is that the composite material is doped with silver and filled in the pores of the hard carbon, which reduces the side reactions of the material with the electrolyte, can improve the initial efficiency of the material and its compatibility with the electrolyte, and improve the storage and cycle performance. The hard carbon material prepared by the embodiment of the present invention has obvious advantages in high-temperature storage performance, because the porous structure of the hard carbon filled with silver material reduces its side reactions and improves the high-temperature storage performance. At the same time, the doped silver has the characteristic of low electronic impedance, which reduces its side reactions during the charging and discharging process and improves the cycle performance. The material contains lithium difluorooxalatoborate to provide sufficient lithium ions to improve the cycle performance.

[0088] The above disclosure is only the preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.

Claims

1. A method for preparing a silver-doped hard carbon composite material, comprising the following steps: Pretreatment of hard carbon materials: soaking the hard carbon precursor in an acid solution to obtain carboxylated hard carbon; Preparation of silver ammonia solution: mixing silver nitrate solution and ammonia solution to obtain silver ammonia solution; Silver doping reaction: mixing the pretreated hard carbon material and the silver ammonia solution, adjusting the pH value to 9-10, adding formaldehyde solution, reacting at a temperature of 50-100° C., filtering and drying to obtain a silver-doped hard carbon precursor; Pre-lithiation of hard carbon: the silver-doped hard carbon precursor is mixed with an organic solution of lithium salt, spray-dried, and carbonized under an inert atmosphere to obtain the silver-doped hard carbon composite material.

2. The method for preparing the silver-doped hard carbon composite material according to claim 1, characterized in that: The acid solution is selected from at least one of sulfuric acid, hydrochloric acid, nitric acid and phosphoric acid, and the mass concentration of the acid solution is 5-20%.

3. The method for preparing the silver-doped hard carbon composite material according to claim 1, characterized in that: The hard carbon precursor and the acid solution are mixed and kept at 50-100° C. for 24-72 hours.

4. The method for preparing the silver-doped hard carbon composite material according to claim 1, characterized in that: When preparing the silver ammonia solution, the mass concentration of the silver nitrate solution is 1-5%, the mass concentration of the ammonia solution is 5-20%, and the mass concentration of the formed silver ammonia solution is 3-15%.

5. The method for preparing the silver-doped hard carbon composite material according to claim 1, characterized in that: The volume ratio of the silver nitrate solution to the ammonia solution is 1:1-2.

6. The method for preparing the silver-doped hard carbon composite material according to claim 1, characterized in that: In the silver doping reaction, the ratio of the carboxylated hard carbon, the silver ammonia solution and the formaldehyde solution is 10-50 g:100 mL:10-50 mL.

7. The method for preparing the silver-doped hard carbon composite material according to claim 1, characterized in that: The lithium salt is selected from one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(trifluoromethylsulfonyl imide), lithium bis(fluorosulfonyl imide), lithium bis(oxalatoborate), lithium difluorooxalatoborate and lithium difluorophosphate.

8. The method for preparing the silver-doped hard carbon composite material according to claim 1, characterized in that: The mass ratio of the silver-doped hard carbon precursor to the lithium salt is 100:1-5.

9. A silver-doped hard carbon composite material prepared according to the method for preparing a silver-doped hard carbon composite material according to any one of claims 1 to 8.

10. Use of the silver-doped hard carbon composite material according to claim 9 as a negative electrode material for a battery.